Aspectos pragmáticos y estratégicos del desarrollo de la destreza de expresión escrita en Filología Española en la tercera década del siglo XXI - Grabowska, Monika; Krzyżostaniak, Magdalena (Studia Romanica Posnaniensia, 2021)
Written expression is one of the most important skills in philological studies. Subjected to a constant formative and summative evaluation, it plays a distinctive role and shows both the achievements and the shortcomings of the student’s linguistic, sociolinguistic and pragmatic skills. In this analysis, we would like to focus on this last component of communicative competence, but also on the strategies of the learners connected with their practice of various forms of writing in the academic and private sphere. The paper summarizes the results of a survey completed by Spanish philology students from the Department of Romance Philology at the University of Wroclaw during the summer term of 2018/2019 academic year. One of the objectives of the survey was to find out to what extent the PNJH Pisanie program corresponds to the needs and expectations of current students in Poland.